2021
DOI: 10.1007/s00404-021-06192-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative and postoperative complications of gynecological laparoscopic interventions: incidence and risk factors

Abstract: Purpose The aims of this study were to determine the incidence of intraoperative and postoperative complications of laparoscopic gynecological interventions and to identify risk factors for such complications. Methods All patients who underwent laparoscopic interventions from September 2013 to September 2017 at the Department of Gynecology, Obstetrics and Reproductive Medicine, Saarland University Hospital were identified retrospectively using a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
3
10
0
4
Order By: Relevance
“…The overall minor complications such as port site discomfort/pain and minimal bleeding during surgery were <2%, and major complications such as port site hernia, bowel injury/bowel ischemia/gangrene, or massive bleeding due to vessel injury were <1% [ 26 ]. Acceptable low morbidity and complications were seen in the current study and have been similarly reported in the literature [ 27 , 28 ]. The limitations of the current study are as follows: in India, we have four different robotic platforms approved for clinical use, and under this study, all cases were operated by the da Vinci system, and not all centers in India performing RALS for gynecological cases have participated for the study.…”
Section: Discussionsupporting
confidence: 88%
“…The overall minor complications such as port site discomfort/pain and minimal bleeding during surgery were <2%, and major complications such as port site hernia, bowel injury/bowel ischemia/gangrene, or massive bleeding due to vessel injury were <1% [ 26 ]. Acceptable low morbidity and complications were seen in the current study and have been similarly reported in the literature [ 27 , 28 ]. The limitations of the current study are as follows: in India, we have four different robotic platforms approved for clinical use, and under this study, all cases were operated by the da Vinci system, and not all centers in India performing RALS for gynecological cases have participated for the study.…”
Section: Discussionsupporting
confidence: 88%
“…Endometriosis therapy focuses on pain relief, improvement of fertility or the prevention of organ dysfunction [1]. In addition to medical interventions, a laparoscopic approach is generally accepted as the mainstay to remove endometrial implants and restore anatomy [2,3]. For peritoneal endometriosis, this is commonly achieved by different minimally invasive techniques such as sharp excision and subsequent haemostasis, ablation with monopolar or bipolar energy, CO 2 laser vaporization, thermal destruction with helium plasma as well as ablation with plasma technology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding is not the only problem encountered during the surgical treatment of large uterine myomas; the need for intracorporal reconstruction of the uterine wall with its excessive cut edges due to expansion of the myometrial layer by a large intramural fibroid also poses another challenge. This procedure can result in excessive blood loss requiring transfusion, prolongation of the operating time, and postoperative complications requiring prolonged hospital stays [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%